IMPROVING READING COMPREHENSION OF NARRATIVE TEXT THROUGH STUDENTS’ TEAM ACHIEVEMENT DIVISION (STAD) - Sudaryanto, Meidi; Marbun, Rismaya; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research is aimed at improving students? reading comprehension of narrative text. This research was conducted to second year students of SMK Al-Madani Pontianak in academic year 2013/2014. This class consists of 30 students. The researcher conducted a classroom action research. The data was collected by using observation and measurement technique. The observation checklist and field notes were used as the tools of data collecting. Students? Team Achievement Division (STAD) was used as technique in this research. The researcher applied three cycles. The research findings showed that the mean score of students? reading comprehension in the first cycle was 55.36; the second cycle was 58.33 but in the third cycle was 62.03. From the research applied to the subject of the research, it can be stated that the Students? Team Achievement Division (STAD) could ensure the students in understanding and comprehending the text they read. Keywords: Reading Comprehension, Narrative Text, STAD Abstrak: Penelitian ini bertujuan untuk meningkatkan pemahaman membaca teks naratif siswa. Penelitian ini dilakukan pada siswa kelas dua SMK Al-Madani Pontianak pada tahun akademik 2013/2014. Kelas ini terdiri dari 30 siswa. Peneliti melakukan penelitian tindakan kelas. Pengumpulan data dilakukan dengan menggunakan observasi dan teknik pengukuran. Ceklis pengamatan dan catatan lapangan digunakan sebagai alat pengumpulan data. Students? Team Achievement Division (STAD) digunakan sebagai teknik dalam penelitian ini. Peneliti diterapkan tiga siklus. Hasil penelitian menunjukkan bahwa nilai rata-rata dari pemahaman membaca siswa pada siklus I adalah 55,36; siklus kedua adalah 58,33 tapi pada siklus ketiga adalah 62,03. Dari penelitian yang diterapkan pada subjek penelitian, dapat dinyatakan bahwa Students? Team Achievement Division (STAD) bisa menjamin siswa dalam memahami dan memahami teks yang mereka baca. Kata Kunci: Pemahaman Membaca, Teks Naratif, STAD